2018
DOI: 10.31031/pps.2018.01.000517
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Fuel Oil Recovery from Oil Sludge by Multiple Extraction Processes

Abstract: Oil sludge from the bottom tank of shipping process was used to extract heavy fuel oil using multiple extraction techniques. Solvent extraction is necessary to recover valuable hydrocarbon from oil sludge and to reduce the volume of waste sludge so a further reduction in oil sludge has an impact effect on land and water. This process used methyl ethyl ketone (MEK) at different operating temperatures from room temperature to 50 ᵒC and different solvent to sludge ratios. The percent recovery of heavy fuel oil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They found that the optimal temperature, solvent concentration, rotation speed, treatment time, and pH was 30 • C, 2.0 g•L −1 , 200 rpm, 60 min; and 11, respectively. Al Zubaidi [120] proposed a multistage extraction procedure to maximize oil recovery. The separate experimental results by Tian [121] and Hou et al [119] all suggested that ionic liquids could effectively decrease the heavy oil interaction force.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…They found that the optimal temperature, solvent concentration, rotation speed, treatment time, and pH was 30 • C, 2.0 g•L −1 , 200 rpm, 60 min; and 11, respectively. Al Zubaidi [120] proposed a multistage extraction procedure to maximize oil recovery. The separate experimental results by Tian [121] and Hou et al [119] all suggested that ionic liquids could effectively decrease the heavy oil interaction force.…”
Section: Solvent Extractionmentioning
confidence: 99%